The Poetry of James Joyce Reconsidered - Conner, Marc C., 1965- (Book collections on Project MUSE., 2012)
To many, James Joyce is simply the greatest novelist of the twentieth century. Scholars have pored over every minutia of his public and private life from utility bills to deeply personal letters in search of new insights into his life and work. Yet, for the most part, they have paid scant attention to the two volumes of poetry he published. The nine contributors to The Poetry of James Joyce Reconsideredconvincingly challenge the critical consensus that Joyce's poetry is inferior to his prose. They reveal how his poems provide entries into Joyce's most personal and intimate thoughts and ideas. T.